Safety and efficacy of romiplostim in children with acquired aplastic anemia who are naïve to immunosuppressive therapy - Mohammadreza Bordbar; Alireza Faghihi; Omid Reza Zekavat; Mahdi Shahriari; Shayan Bordbar (Haematologica)
Not available.